2014
DOI: 10.5578/mb.8080
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Use of Serological Tests for Hepatitis B Virus in Evliya Celebi Education and Research Hospital of Dumlupinar University, Kutahya

Abstract: ÖZETCiddi klinik tablolara yol açması ve kronikleşmesi nedeniyle hepatit B virusu (HBV) enfeksiyonunun tanısında laboratuvar testlerinin doğru kullanılması ve yorumlanması oldukça önemlidir. Tüm HBV belirteçleri için serolojik testlerin kullanılması yüksek maliyet, iş gücü ve zaman kaybına yol açtığından, bu amaçla tanısal algoritmalardan yararlanılır. Bu retrospektif çalışmada, HBV enfeksiyonu serolojisinde uygunsuz test istemlerinin sayısı ve oluşturduğu mali yükün belirlenmesi, ayrıca gereksiz test istemler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…In our study, the cost of unnecessary test requests is lower than other studies [8,9] . However, an amount of TL 1507 unnecessarily consumed state resources.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, the cost of unnecessary test requests is lower than other studies [8,9] . However, an amount of TL 1507 unnecessarily consumed state resources.…”
Section: Discussioncontrasting
confidence: 50%
“…Therapeutic drugs monitoring makes no exception to this rule, wherein inappropriateness of test ordering for monitoring theophylline and digoxin plasma values was found to be as high as 64.2% (13) and 45% (14) of all requests, respectively. As regards infectious diseases testing, Genç and Aksu estimated that between 37-45% of all serological tests for hepatitis B virus (HBV) may be avoidable (15).…”
Section: Introductionmentioning
confidence: 99%
“…At this same hospital, it was detected that 12.9% of anti-HBs, 12.9% of anti-HBc total, 74.8% of anti-HBc immunoglobulin M (IgM), 83.9% of hepatitis B envelope antigen (HBeAg), and 75.2% of anti-HBe tests were unnecessary, at a total cost of 56.153 Turkish liras (TL) (4). Genc and Aksu (5) found that the percentages of unnecessary test requests were 2.23% in anti-HBs, 0.7% in anti-HBc total, 37.41% in anti-HBc IgM, 44.86% in HBeAg, and 37.75% in anti-HBe at a tertiary care hospital, and those tests led to an average annual financial burden of 14.000 TL.…”
Section: Dear Editor;mentioning
confidence: 99%
“…Warning signals that are situated within hospital network systems may report to the physician previous test results. Thus, the physician may not request the tests again (5). Another technique for preventing duplicate tests is organizing education about diagnostic algorithms for health professionals (4).…”
Section: Dear Editor;mentioning
confidence: 99%
See 1 more Smart Citation